Exploring postgraduates’ experiences: A focused group discussion on violence against doctors - Vijayalaxmi Mangasuli; S. B. Vijeth; Bhagyalaxmi Sidenur; A. M. Amrutha (Journal of Current Research in Scientific Medicine)
Background: Workplace violence against physicians is a major occupational hazard worldwide. This study explored doctors’ experiences and perspectives on violence through focus group discussions. Materials and Methods: Four focus groups were conducted with 36 postgraduate trainees from various specialties at a hospital in Karnataka, India. Discussions were audio-recorded, transcribed verbatim, and analyzed thematically. Results: Verbal abuse was the most prevalent form of violence experienced, followed by threats and physical assaults. Key factors precipitating violence included long waits, unmet expectations, miscommunication, and distrust on doctors. Impacts included increased staff stress, compromised care due to delays or avoidance of high-risk situations, and lasting psychological effects. Suggested interventions were improved security, training in de-escalation, zero-tolerance policies, and support systems for affected staff. Conclusion: This study provides evidence that workplace violence remains a critical issue for doctors in India. Multifaceted strategies are urgently needed focusing on training, communication, security, and policies to prevent and address violence. Further research should investigate risk factors and interventions.